Efek Kombinasi Pupuk Organik Sludge dan Pupuk NPK Mutiara Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays L. saccharata Sturt) - Camalia, Rafa Adilla Zakhirah; Agustini, Rika Yayu; Wagiono, Wagiono Wagiono (UNIVERSITAS LABUHANBATU, 2024)
Sludge is formed from the waste of food and beverage industry, that can be processed into organic fertilizer and utilized for agriculture, so that the combination of sludge organic fertilizer and NPK Mutiara fertilizer can increase the growth and yield of sweet corn plants (Zea mays L. saccharata Sturt). The aim of this research is to determine the best combination of organic sludge fertilizer and NPK Mutiara fertilizer for the growth and yield of sweet corn plants (Zea mays L. saccharata Sturt). The research was conducted on land owned by the Republic of Indonesia Money Printing Company (PERURI) from January to April 2024. The method used was a single-factor Randomized Block Design (RBD) with 7 treatments and 4 replications, resulting in 28 experimental units consisting of: A (Control), B (Sludge 10 t/ha + NPK 300 kg/ha), C (Sludge 15 t/ha + NPK 300 kg/ha), D (Sludge 20 t/ha + NPK 300 kg/ha), E (Sludge 10 t/ha + NPK 400 kg/ha), F (Sludge 15 t/ha + NPK 400 kg/ha), G (Sludge 20 t/ha + NPK 400 kg/ha). The results of the experiment were tested with the F test, if it had a significant effect, it was further tested with the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that treatment G significantly affected the growth and yield of sweet corn plants. Treatment G (Sludge 20 t/ha + NPK 400 kg/ha) gave the highest result for plant height aged14,21,28,35,and42hst, number ofleavesaged21,28,35,and42hst, stemdiameter14,21,28,35,and42hst,cob length (36.40 cm), cob diameter (67.60 mm), corn cob weight with husk (534.00 grams), corn cob weight without husk (354.25 g), wet stover weight (592.00 g), dry stover weight (345.25), but it does not have a significant effect on the number of rows per cob with an average of (13.64 rows). Keywords: sweet corn, organic sludge fertilizer, NPK mutiara fertilizer.